Evaluation of the Community-Based Hypertension Management Programs in China - Hao, Guang; Chen, Zuo; Wang, Xin; Zhang, Linfeng; Kang, Yuting; Zheng, Congyi; Chen, Lu; Wang, Zengwu; Gao, Runlin (Frontiers in Public Health, 2022)
Purpose: The Chinese government issued the National Essential Public Health Services Package (NEPHSP) in 2009. However, the data are limited for the comprehensive evaluation of NEPHSP on hypertension management. Methods: Data from China Hypertension Survey (CHS). The participants (n=119,412) who were aged ≥35 years with hypertension were included in the final analysis. Further, a total of 64,188 hypertensive patients who were aware of having hypertension were included to evaluate the effect of NEPHSP, and were divided as intervention and control group according to whether or not were covered by the NEPHSP. Blood pressure (BP) was measured after sitting at rest for 5 minutes, by trained staff using a validated digital portable monitor in local communities or clinics. Results: Overall, the coverage of the NEPHSP was 25.6% and increased with age in Chinese adults aged ≥35 years with hypertension. The coverage of NEPHSP was significantly higher in women than in men (P <0.001). A total of 64, 188 hypertensive patients who were aware of having hypertension were included to evaluate the effect of NEPHSP. Compared to the control group, the mean systolic and diastolic BP were 2 mmHg and 1.6 mmHg lower in the NEPHSP group, respectively. The treatment of hypertension was significantly higher in the intervention group than the control group (93.0% vs. 81.4%, P<0.001), and the control of hypertension was also significantly higher in the intervention group than the control group (35.9% vs. 29.6%, P<0.001). Furthermore, similar trends were found in rural and urban, as well as in men and women. Conclusions: Our results showed that NEPHSP is efficient in hypertension treatment and control in hypertensive patients aged ≥ 35 years in China. However, the coverage of NEPHSP was still lower.